Pengaruh Kualitas Produk dan Kualiatas Layanan Pelanggan terhadap Niat Pembelian Ulang pada Online Fashion Industry di Indonesia - Vera Maria; Komang Windi Yuniantari; Mustika Ayu Cahaya Lintang (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This study aims to analyze the impact of product quality and customer service on repurchase intentions in the online fashion industry in Indonesia. With the rapid growth of this industry, a deep understanding of the factors influencing consumer purchase decisions is crucial. Product quality and customer service are the main focus of this research because both play a central role in shaping customer satisfaction and building long-term relationships between brands and consumers. Through a quantitative approach and the analysis of theories such as customer satisfaction theory, perceived quality theory, and customer loyalty theory, this study seeks to provide insights into how product quality and customer service can influence repurchase intentions. The results of the study show that product quality and customer service have a significant impact on repurchase intentions in the online fashion industry in Indonesia. High product quality increases customer satisfaction and strengthens the relationship between brands and consumers, which in turn increases the likelihood of repurchase. Similarly, good customer service enhances satisfaction and builds strong trust between brands and consumers, which also positively influences repurchase intentions. The practical implications of this study are that companies in the online fashion industry in Indonesia should prioritize improving product quality and customer service to ensure business sustainability and increase customer loyalty.